Recent Issues on Fuzzy Databases - Bordogna, Gloria 1960-; Pasi, Gabriella 1961- (Physica-Verlag HD, 2000)
This book focuses on the recent research issues regarding the application of fuzzy set theory to extend the functionalities of database management systems. During the past five years, the research in this field has moved from a merely theoretical framework mainly addressing the definition of fuzzy extensions of the relational database model to the consideration of other, object-oriented database paradigms, also in relation with their implementation and application in specific contexts (ex. geographic information systems), fuzzy data mining, and fuzzy functional dependencies definition. Besides contributing to stimulate the interest in the field of fuzzy databases, the book has the aim of showing that the research carried out so far has matured some fuzzy extensions of classical databases that are feasible to be implemented and applied fruitfully in real applications
Keywords: Computer Science; Database Management; Artificial Intelligence (incl. Robotics); IT in Business; Earth Sciences, general; Computer science; Information technology; Business / Data processing; Earth sciences; Database management; Artificial intelligence